Hubungan antara Regulasi Diri dan Prokrastinasi Akademik pada Mahasiswa Perantau - Afriza Putri Masyita (Universitas Muhammadiyah Jember, 2023)
Overseas students must adapt to various adjustments and aspects of daily life. In addition, because they are not directly under the authority of their parents, overseas students are more likely to carry out activities independently. This can cause them to neglect their studies and lead to a delay known as academic procrastination. Low self-regulation is one of the factors that have an impact on student procrastination. The method used in this research is quantitative with 137 overseas students as respondents. The scale used is the SSSRQ and APS scale. For sampling, this study employs a purposive sampling strategy. correlation approach The product-moment Pearson was employed in this study as the hypothesis test. Based on the results of testing the hypothesis, it shows that there is a very significant negative relationship between self-regulation and academic procrastination in overseas students.